Review: Understanding fish muscle biology in the indeterminate growth species pacu (Piaractus mesopotamicus) - Perez, Érika Stefani [UNESP]; Duran, Bruno Oliveira Silva; Zanella, Bruna Tereza Thomazini [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (Elsevier, 2023)
The muscle phenotype of fish is regulated by numerous factors that, although widely explored, still need to be fully understood. In this context, several studies aimed to unravel how internal and external stimuli affect the muscle growth of these vertebrates. The pacu (Piaractus mesopotamicus) is a species of indeterminate muscular growth that quickly reaches high body weight. For this reason, it adds great importance to the productive sector, along with other round fish. In this context, we aimed to compile studies on fish biology and skeletal muscle growth, focusing on studies by our research group that used pacu as an experimental model along with other species. Based on these studies, new muscle phenotype regulators were identified and explored in vivo, in vitro, and in silico studies, which strongly contribute to advances in understanding muscle growth mechanisms with future applications in the productive sector.
Keywords: Fish skeletal muscle; Indeterminate growth; Pacu (Piaractus mesopotamicus)